2022
DOI: 10.1007/s11356-022-24061-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses, feeding and survival in the solitary bee Osmia bicornis following exposure to an insecticide and a fungicide alone and in combination

Abstract: In agricultural ecosystems, bees are exposed to combinations of pesticides that may have been applied at different times. For example, bees visiting a flowering crop may be chronically exposed to low concentrations of systemic insecticides applied before bloom and then to a pulse of fungicide, considered safe for bees, applied during bloom. In this study, we simulate this scenario under laboratory conditions with females of the solitary bee, Osmia bicornis L. We studied the effects of chronic exposure to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Icarus® seemed not to have toxicological effects at molecular and behavioural levels on E. fetida at field dose concentrations. A recent study by Martins et al ( 2023 ) showed no toxicological effects in specimens of Osmia bicornis exposed to a tebuconazole-based commercial fungicide. However, some authors report that tebuconazole can induce tumours and developmental anomalies in mice, ocular lesions in dogs and developmental anomalies in rats and rabbits in long-term exposure (Schwarzbacherová et al 2015 ; Coremen et al 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“…Icarus® seemed not to have toxicological effects at molecular and behavioural levels on E. fetida at field dose concentrations. A recent study by Martins et al ( 2023 ) showed no toxicological effects in specimens of Osmia bicornis exposed to a tebuconazole-based commercial fungicide. However, some authors report that tebuconazole can induce tumours and developmental anomalies in mice, ocular lesions in dogs and developmental anomalies in rats and rabbits in long-term exposure (Schwarzbacherová et al 2015 ; Coremen et al 2022 ).…”
Section: Resultsmentioning
confidence: 95%